Effectiveness of Radiofrequency Hyperthermia for Treating Cartilage in Guinea Pigs with Primary Osteoarthritis. (January 2018) - Takahashi, Kenji; Nakamura, Hiroshi; Ozawa, Hitoshi; Hashimoto, Sanshiro; Iijima, Norio; Higo, Shimpei; Watanabe, Hiroshi; Mochizuki, Yusuke; Takai, Shinro
Objective: Autophagy was reported to be essential for maintaining chondrocyte function, and reduced autophagy leads to osteoarthritis (OA). Previous studies showed involvement of heat shock stress in the control of autophagy in cells. This study sought to investigate the effect of hyperthermia on the expression of autophagy-related proteins in articular cartilage and the progression of naturally occurring OA in Hartley guinea pigs. Design: Radiofrequency pulses of 13.56 MHz were applied to the animals' knees for 20 minutes to induce hyperthermia. The knee joints were resected at 8 hours, 24 hours, 72 hours, 7 days, and 6 months after hyperthermia. Serial sections of knees were examined for histopathological changes. The expression levels of Unc-51-like kinase 1 (ULK1) and Beclin1 were analyzed by immunohistochemistry. Results: Analysis of the distribution of positive cells showed that, in cases of moderate OA, ULK1 and Beclin1 expression levels were significantly decreased in the superficial zone (SZ) and middle zone (MZ) ( P < 0.01) compared with normal cartilage. Seven days after exposure to radiofrequency waves, expression levels of ULK1 and Beclin1 were augmented in the SZ in animals with mild OA. The severity of cartilage degradation was significantly reduced ( P < 0.01) in the radiofrequency-treated knees versus the untreated knees. Conclusions: This study showed that heat stimulation enhanced autophagy in healthy knee chondrocytes and chondrocytes in knees with mild OA. The study also showed that long-term periodic application of hyperthermia suppresses aging-related progression of OA. The activation of autophagy by radiofrequency hyperthermia may be an effective therapeutic approach for osteoarthritis.